Effect of hybridization on properties of natural and synthetic fiber‐reinforced polymer composites (2001–2020): A review. Issue 10 (2nd August 2021) - Gupta, M. K.; Ramesh, Manickam; Thomas, Sabu
Abstract: In the past two decades (2001–2020), researchers have been attracted toward hybrid composite materials reinforced with synthetic and natural fibers. Bio‐degradability and harmlessness to the environment are the major attributes of natural fibers, such qualities support these fibers to reinforce into composites. At the same time, higher moisture absorption and poor compatibility characteristics of natural fibers have forced to hybridize with other synthetic/natural fibers. Several researchers have already done the hybridization of natural fibers with synthetic/natural fibers to overcome the limitations of natural fibers. Due to this reason, we perform a literature review on the influence of hybridization on the properties of composites reinforced with synthetic and natural fibers. This review is made on resulting properties of hybrid composites such as mechanical, thermal, water absorption, tribological behavior, morphological characteristics, and other properties from the year 2001 to 2020. Abstract : A review has been performed on the influence of hybridization on the properties of composites reinforced with synthetic and natural fibers. This review is made on resulting properties of hybrid composites such as mechanical, thermal, water absorption, tribological behavior, morphological characteristics, and other properties from the year 2001 to 2020.